Digital human resource management influence on the organizational resilience - Azra Ahmić; Muhamed Ćosić (Organization Management Journal)
Purpose – Given the substantial challenges and disruptions that companies often encounter from within the organization and the broader market landscape – such as market turbulence, technological advancements and regulatory changes – developing robust organizational resilience and transitioning to digital business practices have become top priorities. This paper aimed to explore if digital human resource management (HRM) significantly influences the organizational resilience within the context of emerging economy. Design/methodology/approach – To analyze data collected from HRM experts active in the business sector of Bosnia and Herzegovina, we utilized in this paper multiple regression analysis. This approach allowed us to explore the relationships and impacts within this specific regional context. Findings – The study findings revealed that digital HRM significantly enhances organizational resilience, positively impacting its three key components: the ability to anticipate, the capacity to cope and the capability to adapt. Practical implications – This study offers digital HRM strategies for enhancing organizational resilience, guiding HR professionals in using digital tools to boost employee adaptability, streamline crisis communication and improve flexibility and readiness for future disruptions. Originality/value – This research adds to the existing literature and ensures practical implication on digital HRM and organizational resilience by empirically demonstrating how digital HRM strengthens organizational capabilities to foresee potential disruptions, respond effectively to crises and adapt to changing circumstances. These capabilities help organizations maintain stability and continue operations smoothly during unexpected events, thereby safeguarding their long-term sustainability and competitive edge.